Pendidikan Kesehatan dan Kemandirian Keluarga dalam Merawat Pasien Tuberkulosis di Kecamatan Tuah Madani Kota Pekanbaru - Putri, Amanda Wulandari; Ayub, Daeng; Ramadhani, Masyitha (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: Family participation is essential for tuberculosis care because treatment success depends not only on clinical services but also on daily support, prevention practices, and household-level adherence. This study examined the influence of health education on family independence in caring for patients with tuberculosis in Tuah Madani District, Pekanbaru City. A quantitative ex-post facto design was used with 104 family caregivers selected from a population of 140 families registered in community tuberculosis program records. Data were collected using structured Likert-scale questionnaires measuring health education through understanding, acceptance, and response, and family independence through non-dependence, family confidence, healthy living practices, and emotional self-control. The instruments were tested before field use and showed acceptable reliability after invalid items were removed, with Cronbach’s alpha of 0.867 for health education and 0.942 for family independence. Descriptive analysis showed that health education was high (mean = 4.32), with the strongest indicator being response (mean = 4.46). Family independence was also high (mean = 4.37), and most respondents were in the very high category for independence. Inferential analysis indicated a positive and significant relationship between health education and family independence. The Pearson correlation coefficient was strong, and regression analysis showed that health education explained 61.8% of the variance in family independence. These findings suggest that health education strengthens family capacity to understand tuberculosis, accept treatment requirements, respond to prevention messages, support medication adherence, and maintain a healthier home environment. The study contributes to community education and public health practice by emphasizing the household as a strategic unit for tuberculosis control. Abstrak: Partisipasi keluarga merupakan komponen penting dalam perawatan tuberkulosis karena keberhasilan pengobatan tidak hanya ditentukan oleh pelayanan klinis, tetapi juga oleh dukungan sehari-hari, praktik pencegahan, dan kepatuhan pengobatan di tingkat rumah tangga. Penelitian ini bertujuan menganalisis pengaruh pendidikan kesehatan terhadap kemandirian keluarga dalam merawat pasien tuberkulosis di Kecamatan Tuah Madani, Kota Pekanbaru. Penelitian menggunakan pendekatan kuantitatif dengan desain ex-post facto. Sebanyak 104 anggota keluarga dipilih dari populasi 140 keluarga pasien tuberkulosis yang tercatat dalam program tuberkulosis masyarakat. Data dikumpulkan menggunakan kuesioner pendidikan kesehatan dan kemandirian keluarga yang telah diuji validitas dan reliabilitasnya. Analisis dilakukan secara deskriptif dan inferensial dengan regresi sederhana dan korelasi Pearson. Hasil menunjukkan bahwa pendidikan kesehatan berada pada kategori tinggi dengan rerata 4,32, sedangkan kemandirian keluarga juga berada pada kategori tinggi dengan rerata 4,37. Analisis inferensial menunjukkan hubungan positif dan signifikan antara pendidikan kesehatan dan kemandirian keluarga (p<0,05). Nilai R square sebesar 0,618 menunjukkan bahwa pendidikan kesehatan menjelaskan 61,8% variasi kemandirian keluarga, sementara 38,2% dipengaruhi faktor lain di luar model. Temuan ini menegaskan bahwa pendidikan kesehatan berperan penting dalam memperkuat kemampuan keluarga untuk mendukung pengobatan, mencegah penularan, dan menjalankan perawatan tuberkulosis secara mandiri.